The Effect of VBA for Microsoft Excel as Teaching Material to Improve Prospective Elementary School Teachers' Mathematical Conceptual Understanding - Ruqoyyah, Siti; Murni, Sukma; Wijaya, Tommy Tanu (Universitas Pendidikan Indonesia, 2020)
This research is motivated by the low ability to understand mathematical concepts possessed by prospective elementary school teacher students. This study aims to see the achievement and improvement of students' mathematical understanding abilities that use Microsoft Excel-based VBA teaching materials with those using conventional learning. This study uses a quasi-experimental method with a non-equivalent pre-test and post-test control group design. This study's population were all second-semester elementary school teacher candidates in one private university in West Java, Indonesia. The sample in this study was 70 prospective 2nd-grade elementary school teacher candidates. The instrument used in this study was a test of understanding mathematical concepts. The results showed: 1) learning using VBA Microsoft Excel as a teaching material was able to improve students' ability to understand mathematical concepts; 2) learning using Microsoft Excel VBA as teaching material is better than conventional learning; and 3) students can be enthusiastic, active and motivated in learning mathematics with VBA Microsoft Excel.